2012
DOI: 10.1016/j.juro.2011.09.145
|View full text |Cite
|
Sign up to set email alerts
|

Near Infrared Spectroscopy to Diagnose Experimental Testicular Torsion: Comparison With Doppler Ultrasound and Immunohistochemical Correlation of Tissue Oxygenation and Viability

Abstract: Near infrared spectroscopy is as effective but quicker than Doppler ultrasound for detecting testicular torsion without a radiologist. Near infrared spectroscopy accurately reveals oxygen saturation, which is more vital than blood flow, on which Doppler ultrasound focuses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 20 publications
1
24
0
Order By: Relevance
“…The remaining 17 articles where fully reviewed. Nine articles were finally selected for inclusion in the systematic review after excluding a further eight irrelevant articles (Fig. ).…”
Section: Resultsmentioning
confidence: 99%
“…The remaining 17 articles where fully reviewed. Nine articles were finally selected for inclusion in the systematic review after excluding a further eight irrelevant articles (Fig. ).…”
Section: Resultsmentioning
confidence: 99%
“…Unlike pulse oximetry, the transcutaneous NIRS probe provides a venous weighted tissue %StO2 (approximately 3:1 ratio of venous to arterial blood) and thus is ideal in non-pulsatile or low-flow conditions [33], as would be expected in testicular torsion. NIRS has been studied in sheep, rabbit, and rat models of testicular torsion, demonstrating prompt and consistent identification of significantly lower %StO2 values in torsed versus nontorsed testes [3436]. Recently, our adult human pilot study applying a transscrotal NIRS probe found significantly lower %StO2 values in the affected testis compared to the contralateral, unaffected testis in 11 patients (mean age 18.27 years) with surgically confirmed torsion.…”
Section: New Concepts In Imaging and Testingmentioning
confidence: 97%
“…9 Capraro used testicular tissue oxygen saturation (StO2) measurement to investigate the effect of experimental testicular torsion and surgical relief of torsion in sheep; 10 CW NIRS-derived testicular StO2 has also been measured in a rat model of surgically induced and relieved torsion; 11 and in a similar study in rabbits absolute values of testicular StO2 were obtained using a frequency domain spectrometer with a specially designed optical probe. 12 A dual wavelength CW NIRS device with light emitting diodes (LEDs) as the light source was developed and tested in a rat model using comparison of the ratio of the average intensities of transmitted light at 660 nm to 940 nm obtained in transmission geometry to diagnose torsion. 13 Recently the feasibility of using trans-scrotal NIRS measurement of testicular StO2 to identify the presence of torsion has been demonstrated in adults.…”
Section: Ntroductionmentioning
confidence: 99%